Kajian Agresivitas Pajak: Peran Keberadaan Wanita di Dewan Komisaris, Kepemilikan Manajerial, dan Kebijakan Hutang - Yunita Waryani; Desi Lammarito Sinaga; Zaitul Zaitul; Desi Ilona; Mardiana Azizah (Pusat Riset dan Inovasi Nasional, 2024)
The tax aggressiveness importance’s have been documented by prior researchers. However, prior investigators failed to see it from an agency’s perspective. Therefore, this study determines the effect of agency related variables (women in commissioner board, managerial ownership, and debt policy) on tax aggressiveness. The object of this research is Indonesia listed operating at mining sector. The sample of this research is fifteen companies during 2016 to 2018. secondary hand collected data is employed in this study. The data is analyzed using regression analysis. The result show that Women in commissioners board has significant influence on tax aggressiveness. In addition, debt policy and managerial ownership had no relationship with tax aggressiveness. Out of three control variables, company size has a negative influence on tax aggressiveness at 10%. However, a company’s age and probability have no significant connection to tax agressiveness.